Principales causas de mortalidad en la Región La Libertad, 2010 - Bejarano Acevedo, José Grimaldo (2014)
For this research the following problem was posed: What are the main causes of mortality in the Region La Libertad, 2010 , with the overall objective of determining the leading causes of mortality in the Region La Libertad ? . The databases mortality records were obtained from the Office of Information Technology, Telecommunications and Statistics ( OITE ) of the Regional Health Freedom ( DIRES - LL). The findings of the research were : of the 5 leading causes of death , the leading cause of death are diseases of the circulatory system with 1324 deaths up 33% of the deaths, the second cause of death are tumors with 1118 deaths make up 28 % , the third cause of death are diseases of the respiratory system with 973 cases that make up the 24% , the fourth leading cause of death for injuries and poisoning are 559 cases that make up 14 % for the fifth cause of death has certain infectious and parasitic diseases. The mortality rate by sex varies according to each province , we found that the higher mortality rates for men are found in the digestive system diseases in the provinces of Ascope (70/ 100) , Chepén (100 /100) and Trujillo (83 /100) and the highest mortality rates for the age group of 0-14 years of age is found in certain infectious and parasitic diseases in the provinces of Ascope (8/ 100) , Chepén (7/ 100) Julcán (71/ 100) , Sánchez Carrión (33/ 100), the highest rate for the age group 15-64 years in diseases of the digestive system in the provinces of Ascope (42/ 100) , Chepén ( 82/100 ), Trujillo (81/ 100), Santiago de Chuco (69/100) and the highest rate for the age group 15-64 years of tumors in the Province of Trujillo (77/ 100), Otuzco (83/100), Pataz (80/100), Sanchez Carrion (53/100)